Performa Bobot Badan Akhir, Bobot Karkas serta Persentase Karkas Ayam Merawang pada Keturunan dan Jenis Kelamin yang Berbeda - Nuraini Nuraini; Zikril Hidayat; Kiki Yolanda (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
Merawang chicken is one of the native chickens from Gallus-gallus species, family Phasianidae. Merawang chicken is a local chicken from Merawang Village, Merawang District, Bangka Regency, Bangka Belitung Islands Province and is a genetic source and community asset of Bangka Island Province. Merawang chicken has the potential to be developed as a dual-purpose chicken producing eggs and meat. The research was conducted at the Petaling trial garden, BPTP Kepulauan Bangka Belitung in January 2017. This study aims to determine the performance of first and second breed Merawang chicken both male and female on the final body weight, carcass weight and carcass percentage. The materials used were 24 Merawang chicken, each of which was 12 for the first breed and the second breed and distinguished by sex. The experimental design used was a Complete Randomized Block Design consisting of 2 treatments and 3 replications and one observation unit as many as 2 heads. Data were analyzed statistically by ANOVA and Duncan test with 95% confidence interval. The variables observed in this study include the final body weight, carcass weight and carcass percentage. The results of the variance analysis showed thatthere were no differences in performance between the first breed of Merawang (F1) and the second breed (F2). Sex differences have a significant effect (P≤0.05) on the final body weight, carcass weight and percentage of carcass in Merawang chicken.